Strategies for Implementing Innovation in Romanian SMEs - Daniel RUSU; Maria FRANGIEH (Communications of International Proceedings, 2021)
The main objective of this article is to explore the specific innovation strategies used by responsible leaders of SMEs in order to implement innovation in the organizations they represent to achieve the assumed performance objectives. This case study involved managers from randomly selected SMEs, with relevant practice and experience in the process of implementing innovation in their companies. Interviews were conducted with the participants in order to obtain a perspective and a broader understanding of the most appropriate innovation strategies needed to improve the results obtained in relation to the assumed performance objectives. A complementary and detailed research of press releases, procedures, policies and internal documents provides special information on the implementation in the workplace of innovation practices that support the optimization of productivity compared to the results obtained compared to the established performance objectives. According to the results of the study, the role of senior management in promoting an innovative organizational culture, recognizing ideas as a starting point for innovation and identifying customers as fundamental resources for the organization is particularly important. The implementation of the conclusions of this study supports the establishment of new jobs, supports the economy in cases of recession and contributes to economic development. SMEs have a positive effect on community development by increasing the number of jobs. The findings of this study are able to contribute to local economic development. Investigating the strategies needed to successfully implement innovation in SMEs leads to useful directions for SME managers.
Keywords: Strategy; SMEs; Innovation; Leadership